FROM SOCIAL TIES TO SPATIAL BELONGING: RETHINKING HOME IN REFUGEE STUDIES WITH A FOCUS ON DEEP HALDAR’S BLOOD ISLAND - Patnaik, Sudhir Kumar; Gouda, Nikhil Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The forced displacement of millions due to war, persecution, and environmental disasters presents a significant challenge to the international community. Refugee Studies, a field dedicated to understanding the experiences of refugees, has traditionally focused on social interaction and integration. However, this emphasis overlooks the profound impact displacement has on refugees’ sense of place and home. This article argues that a more nuanced understanding of the refugee experience requires incorporating insights from spatial theory and the concept of "home tactics." The article begins by examining the limitations of the dominant social interactionist paradigm in Refugee Studies. It critiques the "nomadic subjectivity" model, which views refugees as essentially mobile, and the policy-oriented use of "place rootedness" as a tool for resettlement. Drawing on the work of Catherine Broome, the article proposes a more nuanced understanding of the relationship between refugees and place. This includes acknowledging the strategic use of place claims for political purposes while recognizing the genuine emotional attachment refugees have to their lost homes. The concept of "home tactics," developed by Mariano Ortega, offers a valuable framework for understanding how refugees navigate displacement. Home tactics refer to the everyday actions and practices refugees undertake to create a sense of familiarity and belonging in their new environments. The article explores how home tactics transcend economic and political strategies, reflecting deeply personal and emotional connections to land and space. The book "Blood Island" by Deep Haldar serves as a powerful case study for examining home tactics in action. The article analyzes how displaced Bengalis in Dandakaranya recreate a sense of home through rituals like the "Posto Mela" harvest festival. These performative acts connect them to their past and the land they lost. Furthermore, the article explores the embodied dimensions of home and belonging, highlighting the profound sensory connection refugees maintain with their lost homelands. The article concludes by emphasizing the importance of studying refugee narratives to gain deeper insights into their experiences. By analyzing narratives, we can move beyond theoretical frameworks and understand how refugees themselves perceive displacement, place, and home. Incorporating these insights into refugee policy and practice is crucial for developing ethical and sustainable responses to the ongoing global refugee crisis.